2018
DOI: 10.1186/s13293-018-0208-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic metabolic responses mediated by CRF2 receptor during nutritional stress in mice

Abstract: BackgroundChronic stress is a major contributor in the development of metabolic syndrome and associated diseases, such as diabetes. High-fat diet (HFD) and sex are known modifiers of metabolic parameters. Peptide hormones corticotropin-releasing factor (CRF) and urocortins (UCN) mediate stress responses via activation and feedback to the hypothalamic-pituitary-adrenal (HPA) axis. UCN3 is a marker of pancreatic β-cell differentiation, and UCN2 is known to ameliorate glucose levels in mice rendered diabetic with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
7
20
0
Order By: Relevance
“…[ 45 ] In the study by Paruthiyil et al., after HFD (60% kcal from fat) feeding for 8 weeks, only males had hyperinsulinemia and altered lipid profile. [ 48 ] This hyperinsulinemia presented only in male mice was also observed by Wu et al. after 14 weeks of exposure to an HFD 45% kcal from fat.…”
Section: Animal Model Characteristicssupporting
confidence: 62%
See 1 more Smart Citation
“…[ 45 ] In the study by Paruthiyil et al., after HFD (60% kcal from fat) feeding for 8 weeks, only males had hyperinsulinemia and altered lipid profile. [ 48 ] This hyperinsulinemia presented only in male mice was also observed by Wu et al. after 14 weeks of exposure to an HFD 45% kcal from fat.…”
Section: Animal Model Characteristicssupporting
confidence: 62%
“…[45] In the study by Paruthiyil et al, after HFD (60% kcal from fat) feeding for 8 weeks, only males had hyperinsulinemia and altered lipid profile. [48] This hyperinsulinemia presented only in male mice was also observed by Wu et al after 14 weeks of exposure to an HFD 45% kcal from fat. [49] This convergent observation regarding insulin homeostasis is important in the context of this study since insulin resistance is one of the diagnostic criteria for the MetS.…”
Section: Sex Of Animalssupporting
confidence: 62%
“…CRF 1 activation initiates HPA responses and anxiety-like behavior, whereas CRF 2 activation brings systems back to homeostasis, and mediates anxiolytic behavior [11,12]. We have shown that CRF 2 plays a vital role in mediating metabolic [13] and immune responses [14,15,16,17,18,19]. CRF 2 receptor dysfunction is known to exacerbate edema, necrosis, and delayed healing [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…The high-fat diet-induced obese mice are commonly used as a model of insulin resistance. As noted in previous studies, the male mice were more severely affected by the high-fat diet (HFD) than the female mice [ 46 48 ]. In our study, we found that both the male and female HFD-fed mice exhibit insulin resistance and impaired glucose tolerance, but the impairments are worse in the male mice compared to the female mice.…”
Section: Discussionmentioning
confidence: 95%